Sorption ability of the composite sorbent for water treatment from radioactive elements - Gonets A. V. Anna Vladimirovna; Chubik M. P. Maksim Petrovich; Chubik M. V. Marianna Valerianovna; Tretyakov A. N. Aleksey Nikolaevich (Materials and technologies new generations, 2015)
Title screen